On bathos : literature, art, music - Crangle, Sara; Nicholls, Peter, 1950- (Continuum, 2010)
While the sublime has garnered a great deal of critical attention over the past twenty years, its counterpart, bathos, has yet to receive any extended treatment. Generally understood as an inadvertent descent to the low, vulgar, and ludicrous in writing or art, the term "bathos" was popularised by Pope, who used it to satirise his contemporaries. Ironically likening bathos to the depths of profundity, Pope lauded his peers for their influential writings whilst openly deriding their absurd misuses of figure and rhetorical device. Pope's method proved prophetic: today, artists regularly celebrat.